2015
DOI: 10.21138/bage.1821
|View full text |Cite
|
Sign up to set email alerts
|

Los centros de interpretación como motor de desarrollo turístico local, ¿un modelo fracasado? El caso de la provincia de Cádiz

Abstract: RESUMENEste texto tiene como finalidad el análisis de los centros de interpretación existentes en los municipios de la provincia de Cádiz planteándose como hipótesis de trabajo la conveniencia para la oferta turística provincial de este tipo de centros y la necesidad de realizar cambios en la planificación y en la gestión de estos establecimientos tanto desde el punto de vista territorial como social y comercial. El uso del concepto de centro de interpretación es relativamente reciente. No existen normativas g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…This study revealed that the most valued teaching methodologies and activities are those that directly involve students and promote direct visits to the natural environment [35,41,62,63,91,92]. Specifically, the results showed a vivid interest in experiencing the gastronomic culture, which reveals the importance of sensory experiences in the appreciation and understanding of the rural environment and its traditions [49,52,[93][94][95].…”
Section: Discussionmentioning
confidence: 97%
“…This study revealed that the most valued teaching methodologies and activities are those that directly involve students and promote direct visits to the natural environment [35,41,62,63,91,92]. Specifically, the results showed a vivid interest in experiencing the gastronomic culture, which reveals the importance of sensory experiences in the appreciation and understanding of the rural environment and its traditions [49,52,[93][94][95].…”
Section: Discussionmentioning
confidence: 97%
“…This is confirmed in different investigations that focus their analysis on the effects of LEADER programmes in such areas as well as the ongoing existence of subsidized business based on tourism projects. (González y Macías, 2014;Arcila y López, 2015;Paül et al, 2016;Navarro et al, 2018;Moriche et al, 2021). The study of Sierra de Gata and the Jerte Valley shows that approximately the 50% of business projects related to tourist accommodation closed after few years of being open (Moriche et al, 2021).…”
Section: Final Remarksmentioning
confidence: 99%
“…This dilemma raised in many regions of emptied Spain where, thanks to different public subsidies, the proliferation of tourist infrastructures have been generated without any prior or potential demand that could justify it. Thus, interpretive centres, auditoriums, museums, exhibition halls, hotels, spas, restaurants and other varied tourist facilities, which have been built or placed in buildings rehabilitated for this purpouse, run into serious difficulties shortly after opening due to a lack of demand (González and Macías, 2014;Arcila andLópez, 2015, Navarro et al, 2016). Territorial resilience, the capacity to adapt and overcome a geographical space in the face of negative situations, should be promoted in these places of the emptied Spain, continuing to generate productive landscapes, instead of just contemplative ones to be consumed by urban tourists.…”
Section: Introductionmentioning
confidence: 99%
“…In the beginning, this proliferation of heterogeneous museum initiatives was associated with a certain ambiguity in its functionality, lack of definition of purpose and absence of perspective. The museum was testing different exhibition models, in its an attempt to find a harmonious and balanced concept that responded on the one hand to its interests as an institution with a vision and a defined mission, and on the other, to the needs and demands of contemporary society [15].…”
Section: Fragile Institutions In Uncertain Timesmentioning
confidence: 99%